A Novel Fluorescent Probe for Determination of pH and Viscosity Based on a Highly Water-Soluble 1,8-Naphthalimide Rotor - Ventsislav V. Bakov; Nikolai I. Georgiev; Vladimir B. Bojinov (Molecules, 2022)
A novel highly water-soluble 1,8-naphthalimide with pH and viscosity-sensing fluorescence was synthesized and investigated. The synthesized compound was designed as a molecular device in which a molecular rotor and molecular “off-on” switcher were integrated. In order to obtain a TICT driven molecular motion at C-4 position of the 1,8-naphthalimide fluorophore, a 4-methylpiperazinyl fragment was introduced. The molecular motion was confirmed after photophysical investigation in solvents with different viscosity; furthermore, the fluorescence-sensing properties of the examined compound were investigated in 100% aqueous medium and it was found that it could be used as an efficient fluorescent probe for pH. Due to the non-emissive deexcitation nature of the TICT fluorophore, the novel system showed low yellow–green emission, which represented “power-on”/“rotor-on” state. The protonation of the methylpiperazine amine destabilized the TICT process, which was accompanied by fluorescence enhancement indicating a “power-on”/“rotor-off” state of the system. The results obtained clearly illustrated the great potential of the synthesized compound to serve as pH- and viscosity-sensing material in aqueous solution.